2011
DOI: 10.1021/es104228q
|View full text |Cite
|
Sign up to set email alerts
|

Apportionment of Motor Vehicle Emissions from Fast Changes in Number Concentration and Chemical Composition of Ultrafine Particles Near a Roadway Intersection

Abstract: High frequency spikes in ultrafine number concentration near a roadway intersection arise from motor vehicles that accelerate after a red light turns green. The present work describes a method to determine the contribution of motor vehicles to the total ambient ultrafine particle mass by correlating these number concentration spikes with fast changes in ultrafine particle chemical composition measured with the nano aerosol mass spectrometer, NAMS. Measurements were performed at an urban air quality monitoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 20 publications
(36 reference statements)
0
25
0
Order By: Relevance
“…In another study of vehicle emissions, Klems et al (2011) correlated spikes in PNCs with fast changes in ultrafine particle chemical composition measured with a nanoaerosol mass spectrometer in order to determine the contribution of motor vehicles to the total ambient ultrafine particle mass. They concluded that motor vehicles contribute 48% of the ultrafine particle mass at their site during a winter measurement , 252-277. http://dx.doi.org/10.1016/j.atmosenv.2012.11.011 Page 31 of 59 period but only 16% in the summer period.…”
Section: Source Apportionmentmentioning
confidence: 99%
“…In another study of vehicle emissions, Klems et al (2011) correlated spikes in PNCs with fast changes in ultrafine particle chemical composition measured with a nanoaerosol mass spectrometer in order to determine the contribution of motor vehicles to the total ambient ultrafine particle mass. They concluded that motor vehicles contribute 48% of the ultrafine particle mass at their site during a winter measurement , 252-277. http://dx.doi.org/10.1016/j.atmosenv.2012.11.011 Page 31 of 59 period but only 16% in the summer period.…”
Section: Source Apportionmentmentioning
confidence: 99%
“…The compositions are sorted by carbon mole fraction. Particles on the far left of the plot contain nearly 100% carbon (unoxidized carbon) and are primarily from nearby motor vehicle traffic (Zordan et al, 2008;Klems et al, 2011). In the middle region, carbon content drops off rapidly as nitrogen, sulfur, and oxygen content increase.…”
Section: Uf-atofmsmentioning
confidence: 99%
“…et al (2008),Klems et al (2011Klems et al ( , 2012, RSMS Atlanta, Georgia, USARhoads et al (2003) Baltimore, Maryland, USALake et al (2003) & Tolocka et al (2004a,b, 2005 Houston, Texas, USAPhares et al (2003) Pittsburgh, Pennsylvania, USABein et al (2005Bein et al ( , 2007Bein et al ( , 2008a,b) & Pekney et al (2006) Wilmington, Delaware, USA Reinard et al (2007) TEM Botswana, Mozambique, Namibia, South Africa, and Zambia Li et al (2003), Posfai et al (2003), & van Poppel et al (2005) Detroit, Michigan, USA Utsunomiya et al (2002, 2004) & Utsunomiya and Ewing (2003) Gwangju, Yeosu, and Taean, South Korea Park et al (2009) & Tumolva et al Analysis of a Cr/Mo/W particle class in Pittsburgh, Pennsylvania, USA, by RSMS. (a) Positive ion spectral representation of the class depicting average peak area versus mass-to-charge ratio.…”
mentioning
confidence: 97%
“…Exposure to elevated nanoparticle concentrations is associated with higher incidences of adverse cardiopulmonary effects (Gong et al, 2008;Knibbs et al, 2011;Maudgalya et al, 2008). In urban environments, nanoparticles arising from secondary sources can account for over 50 % of the nanoparticle number concentration (Klems et al, 2011). Anthropogenic pollution has been suggested to enhance the formation of nanoparticles over forested environments .…”
Section: Introductionmentioning
confidence: 99%